JENIS TANAMAN YANG DIGUNAKAN UNTUK OBAT TRADISIONAL DI KECAMATAN KLUET SELATAN - Julita Sasmi; Nursalmi Mahdi; Samsul Kamal (Universitas Islam Negeri Ar-Raniry, 2017)
A study on the inventory of types of plants used for traditional medicine in South Kluet Subdistrict has been conducted. It aimed to find out the types of plants used as traditional medicine in South Kluet subdistrict. The data were collected by using survey and interview method. The data were analyzed by using qualitative analytic by displaying the form of tables and drawings with local name and scientific name of plants. The results showed that there were 56 species of plants from 34 families were used as medicinal plants in South Kluet subdistrict area. These plants are used by the community to treat and prevent diseases, both internal and external diseases such as fever, cough, headache, stomach pain, colds, seizures and itching of the skin. The types of plants that are often used for medicine are crown plants of gods, sambiloto, god leaves, bandotan, jeringau, and other plant species from familia of Zingiberraceae.